Seasonal Evolution of the Ionospheric Summer Evening and Weddell Sea Anomalies: Antarctic Peninsula Area - Castillo-Rivera, C (Elsevier Ltd, 2025)
Diurnal and seasonal variations of the maximum electron concentration of the ionosphere (NmF2) depart from the expected variations in some geographical regions. These anomalies have been studied since before World War II. The Weddell Sea, Bering Sea, and summer evening anomalies preferably occur in local summer and at the equinoxes. In this paper, the seasonal evolution of the Weddell Sea Anomaly (WSA), is studied in detail for the first time using measured diurnal variations of the maximum electron concentration of the F-region from King George Island (62.2°S, 58.8°W, Chilean station). The data are for low solar activity (September 1986 to March 1987) and high solar activity (September 1988 to March 1989), and are used to determine both NmF2 and the height of maximum, hmF2. There are clear changes from the expected diurnal variation of NmF2 with a midday maximum to an anomalous variation with a nighttime maximum and back to the expected variation. Wavelet analysis and Fourier decomposition of the diurnal variation indicate the predominance of the diurnal component in the expected and anomalous stages. During the transition between these stages the diurnal, semidiurnal and terdiurnal components are comparable. As solar activity increases both the periods of transition and the anomalous stages are shorter. The beginnings (ends) of the transitions and anomalous stages are delayed (anticipated) in high solar activity. While the night-time NmF2 values are higher during high solar activity, the night to day ratio is lower. The diurnal behaviour of NmF2 is compared to results from a first-principles model and to a semi-empirical model and differences discussed. The simple semi-empirical model, which estimates a total transport contribution, is consistent with the now clear effect of neutral wind and neutral concentration on the formation of the WSA, as demonstrated by the use of a model including full chemistry and dynamics constrained to adjust winds to reproduce hmF2. © 2024 COSPAR